2020
DOI: 10.1007/s00440-020-00995-6
|View full text |Cite
|
Sign up to set email alerts
|

Stationary distribution and cover time of sparse directed configuration models

Abstract: We consider sparse digraphs generated by the configuration model with given in-degree and out-degree sequences. We establish that with high probability the cover time is linear up to a poly-logarithmic correction. For a large class of degree sequences we determine the exponent $$\gamma \ge 1$$ γ ≥ 1 of the logarithm and show that the cover time grows as $$n\log ^{\gamma }(n)$$ n log γ ( n ) , where n is the number of vertices. The results are obtained by analysing the extremal values of the stationary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Additionally, our proof implies that whp the hitting and the cover time are both n 1+C+o(1) . Our results complement those of Caputo and Quattropani [11] who showed that if the minimum in-degree is at least 2, stationary values have logarithmic fluctuations around n −1 .…”
supporting
confidence: 90%
See 4 more Smart Citations
“…Additionally, our proof implies that whp the hitting and the cover time are both n 1+C+o(1) . Our results complement those of Caputo and Quattropani [11] who showed that if the minimum in-degree is at least 2, stationary values have logarithmic fluctuations around n −1 .…”
supporting
confidence: 90%
“…Typical distances in G n were studied by van der Hoorn and Olvera-Cravioto [26]. Caputo and Quattropani [11] showed that the diameter of G n is asymptotically equal to the typical distance, provided that δ ± ≥ 2 and ∆ ± = O(1). In our previous work [9], we showed that the diameter has different behaviour if no constraints on the minimum degree are imposed.…”
Section: The Directed Configuration Modelmentioning
confidence: 99%
See 3 more Smart Citations